ANALISIS KREATIVITAS MAHASISWA PGSD DALAM MENDESAIN BAHAN AJAR MATEMATIKA SEKOLAH DASAR BERBASIS MEDIA DIGITAL - Arissona Dia Indah Sari; Afakhrul Masub Bakhtiar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the creativity of students in the Elementary School Teacher Education Program (PGSD) in designing mathematics teaching materials based on digital media. The background of the research is grounded in the demands of 21st-century learning, which emphasize creativity and digital literacy as essential competencies for prospective teachers. The research employed a qualitative approach with a descriptive case study design. The subjects consisted of 12 PGSD students from Universitas Muhammadiyah Gresik selected through purposive sampling. Data were collected through analysis of digital learning media products, observation of the design process, in-depth interviews, and documentation. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The results indicate that students’ creativity in designing digital learning media falls into three categories: high (33%), moderate (50%), and low (17%). Creativity was analyzed based on three main aspects: originality of ideas, pedagogical design quality, and utilization of digital literacy. The findings reveal that students’ digital literacy levels strongly influence the quality of creative products produced. Students with higher digital literacy were able to develop more innovative, interactive, and contextual learning media, while limited technical skills became a major obstacle to creativity. This study concludes that strengthening digital literacy, implementing project-based learning, and providing intensive guidance are essential strategies to enhance the creativity of PGSD students in designing digital learning media